(untitled) (Global Journal of Science Frontier Research, 2023)
The purpose of the study was to examine the challenges affecting effective community participation in potable water management in the Wa-West District of the Upper West Region of Ghana A qualitative approach and a case study design were employed for the research The core objective of the study was to examine the challenges affecting effective community participation in potable water management in the Gbaalwob Chogsia and Gadi communities in the Wa West District in the Upper West Region of Ghana The sample size of the study was seventy-two participants A purposive sampling technique was employed in selecting the participants for the study This included thirty residentseach from the three communities namely Gbaalwob Chogsia and Gadi Also three key officials from the District Assembly and three opinion leaders each from the Gbaalwob Chogsia and Gadi communities sampled for both the interviews and focus group discussion A semi-structured interview guide and a focus group discussion checklist were employed in the data collection Data was analysed thematically Emerged themes from the interviews and the focus group discussion were analysed based on the emerging themes from the data collection It was revealed that inadequate finance is a foremost impediment to effective community participation in water management in the district As a result people are unable to make regular contributions to maintenance services of boreholes when they break down It was therefore suggested that there should be the provision of credit facilities to households who are deprived of diversifying their livelihood to enhance household to effectively contribute monthly towards the borehole s maintenance in the various communities